Сальдо зовнішньої торгівлі послугами - Яковенко, Р. В.; Yakovenko, R.; Соловйова, В. Ю.; Solovyova, V. (Przemysl : Nauka і stadia, 2016)
Тези аналізують роль і значення сфери послуг у сучасній економіці, досліджують позитивне сальдо зовнішньоекономічних послуг України за структурою The theses analyze the role and significance of the sphere of services in the modern economy, investigate the positive balance of foreign economic services of Ukraine by structure
The balance of foreign trade in services
Keywords: cфера послуг; зовнішня торгівля послугами; класифікація зовнішньоекономічних послуг; services sphere; foreign trade in services; classification of foreign economic services